Sistema de tococardiografía digital con procesamiento en una FPGA para el monitoreo materno-fetal. - Pérez, Jairo J.; Vanegas, Juan C.; Saldarriaga, Álvaro J.; Bustamante, John (Biomedical Engineering Journal / Revista Ingeniería Biomédica)
Clinical evaluation on fetuses is related to simultaneous critical aspects such as intensity of uterine contractions, fetal movements, and heart rate. Periodic or transient changes in heart rate are studied and appear in relation to various fetal stimuli as spontaneous or induced movements, uterine contractions, fetal hiccups, and so on. Thus, their evaluation is necessary to obtain constant monitoring in which the frequency and variability are expressed efficiently. This paper presents the development of a cardiotochography system for recording fetal heart rate and intensity of uterine contractions, which is composed by three electronic boards, a digital parallel processing unit, a sounds bell and a screen to acquire non-invasively and process tococardiography's signals.